Materiality as Periphery. (2nd October 2019) - Yonan, Michael
Abstract : This article examines how the materiality of art operates as a periphery in art-historical interpretation. Taking as a case study the Palette of King Narmer (c. 3100 bc ), a famous monument of Egyptian culture, the author explores how it has been interpreted while isolating the role of materiality in writings on it. It begins with a discussion of the palette found in a widely used art-historical survey text, Gardner's History of Art, before turning to a methodological authority for much American art-historical writing, Erwin Panofsky (1892–1968). The article analyzes a sophisticated interpretation of the palette by Whitney Davis (b. 1958), which is both a complication of earlier approaches and a confirmation of their tenets when concerning materiality. It then treats recent archaeological approaches to the palette, arguing that they have done more to credit materiality as part of the object's importance, before turning to the work of Alice Stevenson as an exemplification of how much an emphasis on materiality can bring to light. The article concludes by pondering disciplinary divisions and arguing for a layered, de-centralized critical approach to object analysis.